A prospective, double blind randomised controlled trial on efficacy of laparoscopic uterosacral nerve ablation as an alternative of pharmacotherapy in treatment of chronic pelvic pain - Kushwah, Beenu; Kushwah, Devendra Singh; Pandey, Aparna (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Chronic Pelvic Pain (CPP) is one of the commonest symptomatology in gynaecologist’s outpatient clinics. CPP has a profound impact on a woman’s health and quality of life, including an economic impact through loss of working hours. Treatment for chronic pelvic pain is often unsatisfactory. Present study compares Laparoscopic Uterosacral Nerve Ablation (LUNA) with laparoscopy without pelvic denervation in patients presenting with chronic pelvic pain to our outpatient clinic. Methods: It was a Randomised Controlled Trial Study. After considering inclusion and exclusion criteria, 120 patients were selected, out of which 60 (Group I) had undergone diagnostic laparoscopy and 60 (Group II) had undergone diagnostic laparoscopy with LUNA. Results: The overall success rate for group I and group II were 80%, 78.3% and 66.6% versus 85%, 81.6%, and 83.3% at 3, 6, and 12 months, respectively. However, on subgroup analysis it was found that in patients suffering from Congestive Dysmenorrhoea, there was a significant difference in success rate of both the groups. Conclusions: It was found in present study that there was a benefit for patients with dysmenorrheal, further research in this area is desirable to reach towards a discrete conclusion regarding the benefits of LUNA in patients of CPP.